2020
DOI: 10.3390/ijms21144964
|View full text |Cite
|
Sign up to set email alerts
|

Direct On-Chip Differentiation of Intestinal Tubules from Induced Pluripotent Stem Cells

Abstract: Intestinal organoids have emerged as the new paradigm for modelling the healthy and diseased intestine with patient-relevant properties. In this study, we show directed differentiation of induced pluripotent stem cells towards intestinal-like phenotype within a microfluidic device. iPSCs are cultured against a gel in microfluidic chips of the OrganoPlate, in which they undergo stepwise differentiation. Cells form a tubular structure, lose their stem cell markers and start expressing mature intestinal markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 65 publications
0
54
0
Order By: Relevance
“…Through the addition of a cytokine cocktail of IL-1β, tumor necrosis factor α (TNF-α) and interferon-γ (IFN-γ), they were able to replicate the loss of barrier function observed in irritable bowel disease (Beaurivage et al, 2019). Similar results were achieved using iPSCs which can be induced to undergo differentiation within the Organoplate R to express mature intestinal markers, including markers for Paneth cells, enterocytes and neuroendocrine cells (Naumovska et al, 2020).…”
Section: Intestine Modelsmentioning
confidence: 84%
“…Through the addition of a cytokine cocktail of IL-1β, tumor necrosis factor α (TNF-α) and interferon-γ (IFN-γ), they were able to replicate the loss of barrier function observed in irritable bowel disease (Beaurivage et al, 2019). Similar results were achieved using iPSCs which can be induced to undergo differentiation within the Organoplate R to express mature intestinal markers, including markers for Paneth cells, enterocytes and neuroendocrine cells (Naumovska et al, 2020).…”
Section: Intestine Modelsmentioning
confidence: 84%
“…Having demonstrated that our OCRL KO HK-2 cell lines display hallmarks of the phenotype described previously for cells isolated from Lowe syndrome patients, or in animal Lowe syndrome models, we incorporated our cell lines into a three-lane OrganoPlate ® . OrganoPlate is a recently developed microfluidic platform that allows for the growth of 3D proximal tubules in a microfluidic setup [35][36][37]. Cells were seeded into the top channel, then the middle channel was filled with ECM (collagen I) and the bottom channel was filled with medium.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our human in vitro model could also prove useful in small molecule screens or drug validation, in particular if further improved by replacing HK-2 cells by proximal tubule cells isolated from patients or by generating proximal tubule cells from induced pluripotent stem cells [41,42]. We demonstrated, recently, the on-chip differentiation of pluripotent stem cells into intestinal tubules [37].…”
Section: Discussionmentioning
confidence: 99%
“…A commercially available microfluidic chip, Organoplate, [298] has been employed to develop 3D models of BBB-on-chip, [295] glioma-on-chip, [299] gut-on-chip, [300] and vessel-on-chip. [301] Organoplate is a three-lane microfluidic chip fabricated in www.advancedsciencenews.com www.advancedscience.com microtiter plate format comprising 96 tissue chips that can be used for high-throughput drug screening studies.…”
Section: D Microfluidic Modelsmentioning
confidence: 99%